SVP aider moi !

On consider que A=(x-2) (3x+1)
1) Developper et réduire A
2) Factoriser A
3) Résoudre l'équation : (x-2) (4x-1)
4) Calculer A pour x= -3

2
1)A= X × 3X + X × 1 -2 × 3X - 2 × 1 = 3Xau carré + X - 6X- 2 = 3X au carré - 5X -2
1 . A= x*3x + x*1 + -2*3x +-2*1
=3xau carre + 1x +-6x + -2
= 3x au carre + -5x + -2
2 . A=2*1.5xau carre +(-2.5x)+(-2)
= 2(1.5xaucarre+(-2.5x)+(-2))
4. A=(-3-2)*(3*-3+1)
=-5*(-9+1)
= -5*-10
= 50

Réponses

2014-02-27T17:04:23+01:00
2014-02-27T17:07:11+01:00
1 . A= x*3x + x*1 + -2*3x +-2*1      
        =3xau carre + 1x +-6x + -2       
        = 3x au carre + -5x + -2
2 . A=2*1.5xau carre +(-2.5x)+(-2)       
        = 2(1.5xaucarre+(-2.5x)+(-2))
4. A=(-3-2)*(3*-3+1)       
       =-5*(-9+1)       
        = -5*-10       
        = 50